V-belt
By adopting a subsequent rubber layer and a compressed rubber layer in the V-belt, and using a rubber composition of a specific composition, including polyaramide staple fibers and ethylene-α-olefin elastomers, the problem of insufficient durability of the drive belt is solved, and higher durability and lower replacement frequency are achieved.
Patent Information
- Application Number
- CN202380063359.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-05
- Filing Date
- 2023-08-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-08-02
AI Technical Summary
The existing transmission belts are insufficient for long-term use, resulting in high replacement frequency.
Using a V-belt with a subsequent rubber layer and a compressed rubber layer, the rubber composition meets certain storage elastic modulus and elongation conditions through a specific composition and treatment method, and contains polyaramide staple fibers and ethylene-α-olefin elastomers.
It significantly improves the durability of the V-belt, is suitable for low-speed and high-speed power transmission, and reduces replacement frequency.
Smart Images

Figure CN119816676A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a V-belt. Background Art
[0002] Transmission belts are widely used in general industrial machinery, or transportation equipment such as four-wheeled vehicles and two-wheeled vehicles. Transmission belts are strongly required to have durability so that they can be used for a long time and the frequency of replacement can be reduced. For example, Patent Document 1 proposes a transmission belt with excellent durability using ethylene propylene diene monomer (EPDM) rubber that has excellent weather resistance and cold resistance.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2002-81506 Summary of the invention
[0006] Problems to be solved by the invention
[0007] An object of the present invention is to provide a novel V-belt having excellent durability.
[0008] Technical means of solving problems
[0009] The structure of the present invention for solving the above-mentioned problems is as follows.
[0010] 1. A V-belt, characterized in that it comprises: a core wire extending along the length direction of the belt is embedded in the rubber layer; and
[0011] A compression rubber layer is laminated on the inner circumference of the belt of the adhesive rubber layer.
[0012] Regarding the rubber composition forming the compression rubber layer, when the value of the storage elastic modulus (E') at a dynamic strain of 0.1% strain measured by a tensile method at a frequency of 10 Hz and a test temperature of 25°C based on Japanese Industrial Standards (JIS) K6394 of a rubber composition test piece collected in the belt width direction is X (MPa), and the value of the elongation of the rubber composition test piece collected in the belt length direction is Y (%), the following (1) and (2) are simultaneously satisfied.
[0013] (1) X>800
[0014] (2) Y>-42.05·ln(X)+340
[0015] 2. The V-belt according to 1., characterized in that the rubber composition contains subsequently treated polyaramid short fibers.
[0016] 3. The V-belt according to 1. or 2., characterized in that the rubber composition contains an ethylene-α-olefin elastomer as the rubber component.
[0017] 4. The V-belt according to any one of 1. to 3., characterized in that the rubber composition contains an unsaturated carboxylic acid metal salt.
[0018] 5. The V-belt according to any one of 1. to 4., characterized in that it is a toothed V-belt.
[0019] Effects of the Invention
[0020] The V-belt of the present invention has excellent durability. The V-belt of the present invention has excellent durability in both low-speed and high-speed power transmission, and can reduce the frequency of replacement. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] [ Figure 1 ] is a schematic diagram of a double-tooth V-belt according to one embodiment of the present invention.
[0022] [ Figure 2 ] is a graph showing the relationship between the storage elastic modulus and the elongation of the double-toothed V-belts obtained in the embodiments and comparative examples. DETAILED DESCRIPTION
[0023] The V-belt of the present invention is characterized by comprising: a bonding rubber layer in which a core wire extending in the belt length direction is embedded; and a compression rubber layer laminated on the inner peripheral side of the bonding rubber layer.
[0024] Regarding the rubber composition forming the compression rubber layer, when the value of the storage elastic modulus (E') of the rubber composition test piece collected in the belt width direction at a dynamic strain of 0.1% strain measured by a tensile method at a frequency of 10 Hz and a test temperature of 25°C based on JIS K6394 is X (MPa), and the value of the elongation of the rubber composition test piece collected in the belt length direction is Y (%), the following (1) and (2) are satisfied simultaneously. In addition, "ln" is a natural logarithm.
[0025] (1) X>800
[0026] (2) Y>-42.05·ln(X)+340
[0027] Figure 1 A schematic diagram showing a double-toothed V-belt as one embodiment of the present invention is shown.
[0028] A double-toothed V-belt 1 according to one embodiment includes a belt body 10 formed by laminating and integrating a bonding rubber layer 11, a compression rubber layer 12, and an extension rubber layer 13. The bonding rubber layer 11 has a core wire 111 embedded therein extending substantially in the belt length direction. The compression rubber layer 12 is laminated on the inner circumference of the bonding rubber layer 11, and the extension rubber layer 13 is laminated on the outer circumference of the bonding rubber layer 11. Lower teeth 12a are formed on the inner circumference of the compression rubber layer 12, and upper teeth 13a are formed on the outer circumference of the extension rubber layer 13. A bottom reinforcing cloth 121 is embedded in the compression rubber layer 12 so as to cover the inner circumference of the belt.
[0029] The V-belt of the present invention is not limited to a double-toothed V-belt, and may be a toothed V-belt, a cut-edge V-belt, a wrapped V-belt, a V-ribbed belt, or the like.
[0030] Compression rubber layer
[0031] The cross section of the compression rubber layer 12 in the width direction is an isosceles trapezoidal shape in which the upper base is longer than the lower base, and lower teeth 12a having a substantially sinusoidal cross section in the length direction are arranged at a certain interval along the belt length direction. The compression rubber layer 12 is embedded with a bottom surface reinforcement cloth 121 in a manner covering the inner peripheral surface of the belt, but the bottom surface reinforcement cloth may not be provided.
[0032] The compression rubber layer 12 is formed of a rubber composition. Examples of the rubber component contained in the rubber composition include ethylene-α-olefin elastomers, chloroprene rubber (CR), chlorosulfonated polyethylene rubber (CSM), hydrogenated acrylonitrile rubber (H-NBR), natural rubber (NR), styrene butadiene rubber (SBR), butadiene rubber (BR), nitrile rubber (NBR), etc., and one or more of these may be mixed and used. Examples of the ethylene-α-olefin elastomers include ethylene propylene diene rubber (ethylene propylene diene monomer (EPDM)), ethylene propylene rubber (ethylene propylene monomer (EPM)), ethylene butene rubber (ethylene butene monomer (EBM)), ethylene octene rubber (ethylene octene monomer (EOM)), etc. Among these, it is preferred to contain ethylene-α-olefin elastomer (EPDM, EPM, etc.) and chloroprene rubber (CR), and it is more preferred to contain EPDM. The content of ethylene-α-olefin elastomer in the rubber component is preferably 90% by mass or more, more preferably 95% by mass or more, and further preferably 100% by mass. In addition to the ethylene-α-olefin elastomer, the rubber component may also contain chloroprene rubber (CR), hydrogenated acrylonitrile rubber (H-NBR), natural rubber (NR), etc.
[0033] EPDM preferably has an ethylene content of 40% by mass or more and 60% by mass or less, more preferably 45% by mass or more and 55% by mass or less, and further preferably 50% by mass or more and 53% by mass or less. The diene content of EPDM is preferably 4% by mass or more and 14% by mass or less, more preferably 6% by mass or more and 12% by mass or less, and further preferably 7% by mass or more and 8% by mass or less. As the diene component, dicyclopentadiene (DCPD), 5-ethylidene-2-norbornene (ENB), 1,4-hexadiene (1,4-Hexadiene, 1,4-HD), etc. can be used, and among these, ENB is preferably included. EPDM can also be used in combination of one or more different compositions.
[0034] The EPDM preferably has a Mooney viscosity of 40 or less at 125° C. because the uncrosslinked rubber composition can be uniformly kneaded. The Mooney viscosity is more preferably 35 or less, and even more preferably 30 or less.
[0035] The crosslinking agent for crosslinking the rubber component may also be an organic peroxide, sulfur, polyamine, oxime, or nitroso, and one or more of these may be used. In addition, the rubber composition may also be crosslinked using an electron beam or the like. Of these, an organic peroxide is preferably used in terms of wear resistance.
[0036] As the organic peroxide, a substance that can crosslink the rubber component can be used without particular limitation, for example, di-tert-butyl peroxide, tert-butyl cumyl peroxide, dicumyl peroxide, α,α'-bis(tert-butyl peroxy)-p-diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butyl peroxy)hexane, 2,5-dimethyldi(tert-butyl)hexyne, 2,5-dimethyl-2,5-di(benzoyl peroxy)hexane, tert-butyl isopropyl carbonate, 1,1-bis(tert-butyl peroxy)-3,5,5-trimethylcyclohexane, etc. The organic peroxide can use one or two or more of these. The content of the organic peroxide is usually preferably 0.5 parts by mass or more and 10 parts by mass or less, more preferably 1 part by mass or more and 7 parts by mass or less, and further preferably 2.5 parts by mass or more and 4 parts by mass or less relative to 100 parts by mass of the rubber component.
[0037] The rubber composition preferably contains a co-crosslinking agent. As a co-crosslinking agent, for example, unsaturated carboxylic acid metal salts, N,N'-m-phenylene bismaleimide, ethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, triallyl isocyanurate, etc. can be listed, and one or more of these can be used. The so-called unsaturated carboxylic acid metal salt is a salt of an unsaturated carboxylic acid having at least one carboxyl group and a metal. As unsaturated carboxylic acids, for example, monocarboxylic acids such as acrylic acid and methacrylic acid; dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid can be listed. As metals, for example, zinc, magnesium, calcium, barium, titanium, chromium, iron, cobalt, nickel, aluminum, tin, lead, etc. can be listed. The molar ratio of unsaturated carboxylic acid to metal (the number of moles of unsaturated carboxylic acid / the number of moles of metal) is preferably 2 mol / 1 mol. As unsaturated carboxylic acid metal salts, for example, zinc acrylate, zinc dimethacrylate, magnesium dimethacrylate, etc. can be listed.
[0038] Among these, it is preferred to include zinc dimethacrylate or N,N'-m-phenylene bismaleimide as a co-crosslinking agent. When zinc dimethacrylate is included, its content is preferably 5 parts by mass or more and 60 parts by mass or less, more preferably 10 parts by mass or more and 50 parts by mass or less, and further preferably 25 parts by mass or more and 45 parts by mass or less, relative to 100 parts by mass of the rubber component. When N,N'-m-phenylene bismaleimide is included, its content is preferably 1 part by mass or more and 20 parts by mass or less, more preferably 2 parts by mass or more and 10 parts by mass or less, and further preferably 3 parts by mass or more and 7 parts by mass or less, relative to 100 parts by mass of the rubber component.
[0039] The rubber composition preferably contains short fibers. As short fibers, one or more of para-polyaramid short fibers, meta-polyaramid short fibers, polyparaphenylene benzobisoxazole short fibers, nylon 6 short fibers, nylon 6,6 short fibers, nylon 4,6 short fibers, polyethylene terephthalate short fibers, polyethylene naphthalate short fibers, cellulose fibers, natural fibers such as pulp or cotton, etc. can be used. The short fibers can also be subjected to a resorcinol formalin latex (RFL) treatment by immersing in a resorcinol-formaldehyde-latex aqueous solution and then heating. The blending amount of all short fibers relative to 100 parts by mass of the rubber component is preferably 10 parts by mass or more and 35 parts by mass or less.
[0040] The fiber length of the short fibers is preferably 1 mm to 10 mm, more preferably 2 mm to 3.5 mm.
[0041] The fiber diameter of the short fibers is preferably 5 μm or more and 50 μm or less, more preferably 7 μm or more and 20 μm or less, and still more preferably 11 μm or more and 13 μm or less.
[0042] The staple fibers are an aggregate of filaments, and the fineness of the filaments constituting the staple fibers is preferably 1 dtex (dtex) or more and 5 dtex or less, and more preferably 1.4 dtex or more and 1.6 dtex or less.
[0043] As the short fibers, it is preferred to include polyaramid short fibers, and more preferably to include polyaramid short fibers after subsequent treatment. The polyaramid short fibers are preferably para-type. As the subsequent treatment, any one or more of the following treatments can be implemented, namely, RFL treatment in which heating is performed after immersion in a resorcinol-formaldehyde-latex aqueous solution, subsequent treatment in which drying is performed after immersion in a rubber cement, and subsequent treatment in which heating is performed after immersion in an adhesive solution containing a solution of an epoxy resin or a polyisocyanate resin. The polyaramid short fibers can use two or more different materials, fiber length, fiber diameter, filament fineness, and the presence or absence of subsequent treatment. In the case of including polyaramid short fibers after subsequent treatment, the amount of the polyaramid short fibers after subsequent treatment relative to the rubber composition as a whole is preferably 10 parts by mass or more and 35 parts by mass or less relative to 100 parts by mass of the rubber component, more preferably 15 parts by mass or more and 33 parts by mass or less, and further preferably 20 parts by mass or more and 30 parts by mass or less.
[0044] In addition to these, the rubber composition may also include additives such as reinforcing agents, processing aids, vulcanization accelerators, vulcanization accelerator aids, anti-aging agents, processing oils, anti-scorch agents, ultraviolet absorbers, light stabilizers, softeners, foaming agents, foaming aids, lubricants, flame retardants, antistatic agents, colorants, plasticizers, etc. In addition, in the present invention, these additives are arbitrary and may not be included. However, in the present invention, the so-called "include" means that the concentration of the agent can be used to prepare the agent, and "not include" does not exclude the concentration of not being used to prepare the agent.
[0045] As reinforcing materials, one or more inorganic particles such as silicon dioxide, carbon black, titanium oxide, aluminum oxide, calcium carbonate, magnesium carbonate, zinc carbonate, barium sulfate, diatomaceous earth, clay, talc, zinc oxide, etc. can be deployed. Relative to 100 parts by mass of the rubber component, the deployment amount of the inorganic particles is preferably 10 parts by mass or more, more preferably 20 parts by mass or more. In addition, the upper limit of the deployment amount is preferably 100 parts by mass or less, more preferably 90 parts by mass or less.
[0046] As the inorganic particles, carbon black is preferably used in terms of imparting conductivity, reinforcing properties, and preventing ultraviolet degradation. The carbon black to be blended is not particularly limited, and examples thereof include: channel black; furnace blacks such as super abrasion furnace black (SAF), intermediate super abrasion furnace black (ISAF), N-339, high abrasion furnace black (HAF), N-351, medium abrasion furnace black (MAF), fast extruding furnace black (FEF), semi-reinforcing furnace black (SRF), general purpose furnace black (GPF), extra conductive furnace black (ECF), and N-234; thermal blacks such as fine thermal black (FT) and medium thermal black (MT); acetylene black, Ketjen black EC300J, and Ketjen black EC600JD, and one or more thereof may be blended. Among these, ISAF, HAF and FEF are preferred.
[0047] As processing aids, for example, stearic acid, polyethylene wax, metal salts of fatty acids, etc. can be cited. One or more of these can be used as processing aids. The content of the processing aid is, for example, 0.5 parts by mass or more and 2 parts by mass or less relative to 100 parts by mass of the rubber component.
[0048] Examples of the vulcanization accelerator include thiuram-based (e.g., tetraethylthiuram disulfide (TETD), tetramethylthiuram disulfide (TT), dipentamethylenethiuram tetrasulfide (TRA), etc.), thiazole-based (e.g., 2-mercaptobenzothiazole (MBT), dibenzothiazol disulfide (MBTS), etc.), sulfenamide-based (e.g., N-cyclohexyl-2-benzothiazole sulfenamide (CZ), etc.), and dithiocarbamate-based (e.g., BZ-P, etc.) substances. The vulcanization accelerator may be one or two or more of these. The content of the vulcanization accelerator is, for example, 2 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the rubber component.
[0049] As the vulcanization accelerator, for example, metal oxides such as zinc oxide (zinc white) or magnesium oxide, metal carbonates, fatty acids and derivatives thereof, etc. can be cited. The vulcanization accelerator can use one or two or more of these. The content of the vulcanization accelerator is 3 parts by mass or more and 7 parts by mass or less relative to 100 parts by mass of the rubber component.
[0050] As the anti-aging agent, for example, amine-ketone anti-aging agents, diamine anti-aging agents, phenol anti-aging agents, etc. can be listed. The anti-aging agent can use one or more of these. The content of the anti-aging agent is 0.1 mass parts or more and 5 mass parts or less relative to 100 mass parts of the rubber component.
[0051] As the processing oil, for example, paraffin oil, naphthenic oil, ester oil, aromatic oil, etc. can be cited. One or more of these can be used as the processing oil. The content of the processing oil is preferably 0.1 to 40 parts by mass, more preferably 0.1 to 20 parts by mass, relative to 100 parts by mass of the rubber component.
[0052] When the value of the storage elastic modulus (E') of the rubber composition test piece collected in the belt width direction at a dynamic strain of 0.1% strain measured by a tensile method at a frequency of 10 Hz and a test temperature of 25°C based on JIS K6394 is X (MPa), and the value of the elongation of the rubber composition test piece collected in the belt length direction is Y (%), the rubber composition forming the compression rubber layer of the present invention satisfies the following (1) and (2) at the same time.
[0053] (1) X>800
[0054] (2) Y>-42.05·ln(X)+340
[0055] The storage modulus is a value measured by a tensile method based on JIS K6394:2007, with a strain at a load 1.3 times the load at a load strain of 1% as the average strain, a strain amplitude of 0.1%, a frequency of 10 Hz, and a test temperature of 25° C. The elongation is a value measured based on JIS K6251:2017.
[0056] (1) In order to obtain excellent durability during low-speed driving with a small gear ratio, the value X (MPa) of the storage elastic modulus (E') is preferably 850 MPa or more, more preferably 950 MPa or more, and even more preferably 1000 MPa or more.
[0057] (2) In particular, from the viewpoint of obtaining excellent durability during high-speed driving with a large gear ratio, the elongation value Y (%) of the rubber composition test piece is preferably Y>-42.05·ln(X)+342 or more, more preferably Y>-42.05·ln(X)+345 or more, and even more preferably Y>-42.05·ln(X)+350 or more.
[0058] The bottom reinforcement cloth 121 includes, for example, woven cloth, knitted fabric, nonwoven cloth, etc. formed of synthetic fibers or natural fibers. In addition, a back reinforcement cloth may be provided on the outer peripheral surface of the elongation rubber layer 13. In order to improve the adhesion with the rubber composition, these reinforcement cloths may be subjected to any one or more of the following treatments: RFL treatment in which the cloth is immersed in a resorcinol-formaldehyde-latex aqueous solution and then heated, adhesion treatment in which the cloth is immersed in a rubber cement and then dried, and adhesion treatment in which the cloth is immersed in an adhesive solution containing a solution of an epoxy resin or a polyisocyanate resin and then heated.
[0059] ·Adhesion rubber layer, elongation rubber layer
[0060] The adhesive rubber layer 11 and the elongation rubber layer 13 are both formed of a rubber composition. The rubber composition forming the adhesive rubber layer 11 and the elongation rubber layer 13 can be the same as the rubber composition used to form the compression rubber layer 12, or can be the same as or different from the rubber composition forming the compression rubber layer 12.
[0061] Next, a core wire 111 extending in the longitudinal direction of the belt is embedded in the rubber layer 11 .
[0062] The core wire 111 includes a twisted wire or a filament wire such as polyethylene terephthalate (PET) fiber, polyethylene naphthalate (PEN) fiber, para-aramid fiber, vinylon fiber, etc. In order to improve the adhesion with the rubber composition forming the adhesive rubber layer 11, the core wire 111 may be subjected to any one or more of an RFL treatment of immersing in a resorcinol-formaldehyde-latex aqueous solution and then heating, an adhesive treatment of immersing in a rubber cement and then drying, and an adhesive solution of immersing in an epoxy resin or polyisocyanate resin solution and then heating.
[0063] Manufacturing method
[0064] The method for producing the V-belt of the present invention is not particularly limited, and the V-belt can be produced by a conventional method, for example, the following method can be mentioned.
[0065] Various materials are kneaded to obtain a rubber composition for an uncrosslinked compression rubber layer, and the composition is formed into a sheet shape to obtain an uncrosslinked rubber sheet.
[0066] An uncrosslinked rubber sheet is wound around the outer circumference of a cylindrical mold including lower tooth-forming grooves continuously arranged in the circumferential direction. After a release paper is wound around the outer circumference, a rubber sleeve is covered from above, and the rubber sheet is placed in a vulcanizer and sealed, and steam under high temperature and high pressure is filled into the vulcanizer, and the state is maintained for a predetermined time. At this time, the uncrosslinked rubber sheet flows and is pressed into the lower tooth-forming groove, and about half of the crosslinking is performed at the same time, thereby forming a cylindrical lower tooth complex with lower teeth formed on the inner circumference. At this time, when the rubber sheet contains short fibers, it is preferably arranged in a manner that its texture direction becomes the axial direction of the cylinder, that is, in a manner that becomes the belt width direction.
[0067] After the rubber sleeve is removed and cooled, the outer periphery of the lower tooth complex is ground to adjust the thickness.
[0068] Subsequently, an uncrosslinked rubber sheet for forming a bonding rubber layer is wound on the outer peripheral surface of the lower tooth complex, a core wire is spirally wound thereon, and then an uncrosslinked rubber sheet for forming a bonding rubber layer and an uncrosslinked rubber sheet for forming an elongation rubber layer are sequentially wound thereon to form an uncrosslinked slab.
[0069] The uncrosslinked sheet is covered with a rubber sleeve including upper tooth-forming grooves continuously arranged in the circumferential direction on the inner circumferential surface, and then the uncrosslinked sheet is covered with a second rubber sleeve, which is arranged in a vulcanizing tank and sealed, and the vulcanizing tank is filled with steam at high temperature and high pressure, and the state is maintained for a predetermined time. At this time, the lower tooth composite body is formally crosslinked, and the rubber layer and the core wire are composited and integrated. In addition, the uncrosslinked rubber sheet for forming the elongation rubber layer flows and is pressed into the upper tooth-forming groove, and crosslinked at the same time, thereby forming a cylindrical belt sheet.
[0070] The steam is exhausted from the vulcanizing tank, the seal is released, the rubber sleeve is removed and after cooling, the strip blank is demoulded from the mold.
[0071] After the belt slab is cut into a predetermined width, it is cut so as to form a V-shaped side surface to obtain a double-tooth V-belt.
[0072] Example
[0073] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0074] A compression rubber layer was formed according to the formulation shown in Table 1 below, and a double-toothed V-belt having a circumference of 1200 mm, a maximum width of 33 mm, and a maximum thickness of 16 mm was obtained by the method described above. In addition, the elongation rubber layer and the adhesive rubber layer of the double-toothed V-belt were formed of a cross-linked rubber composition having EPDM as a rubber component. The core wire was composed of twisted yarns of para-polyaramid fibers. The bottom reinforcing cloth was composed of woven cloth of PET fibers.
[0075] The rubber composition forming the compression rubber layer is kneaded with short fibers and chemicals other than the crosslinking agent using a Banbury mixer, and after cooling, the short fibers and the crosslinking agent are added and kneaded.
[0076] [Table 1]
[0077]
[0078] EPDM1: T7241 manufactured by JSR, ethylene content: 52% by mass, ENB content: 7.7% by mass, ML (125°C) 27
[0079] EPDM2: X-4010M manufactured by Mitsui Chemicals, ethylene content: 54% by mass, ENB content: 7.6% by mass, ML (100°C) 8
[0080] EPDM3: EP123 manufactured by JSR, ethylene content: 58% by mass, ENB content: 4.5% by mass, ML (125°C) 19.5
[0081] EPDM4: NORDEL IP 4725P, manufactured by Dow, ethylene content: 70% by mass, ENB content: 4.9% by mass, ML (125°C) 25
[0082] EPDM5: NORDEL IP 4770P, manufactured by Dow, ethylene content: 70% by mass, ENB content: 4.9% by mass, ML (125°C) 70
[0083] Furthermore, the ML (125° C.) of the rubber composition which was a mixture of a plurality of EPDMs used in Examples 2 and 5 was 20.7 and 35.2, respectively.
[0084] Zinc oxide: Zinc oxide 3 types manufactured by Sakai Chemical Co., Ltd.
[0085] Stearic acid: Stearic acid S50 manufactured by Shin Nippon Chemical Co., Ltd.
[0086] Lubricant: Struktol WB16, manufactured by S&S Japan
[0087] Anti-aging agent: Nocrac MB manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0088] ISAF carbon black: Seast 6, manufactured by Tokai Carbon Co., Ltd., arithmetic mean particle size: 22 nm, nitrogen adsorption specific surface area: 119 m 2 / g
[0089] FEF carbon black: Seast SO manufactured by Tokai Carbon Co., Ltd., arithmetic mean particle size: 43 nm, nitrogen adsorption specific surface area: 42 m 2 / g
[0090] Process oil: Sunpar 2280 manufactured by Sun Oil Company
[0091] Co-crosslinking agent 1: trimethylolpropane trimethacrylate (manufactured by Hi-Cross M Seiko Chemical Co., Ltd.)
[0092] Co-crosslinking agent 2: N,N'-m-phenylene bismaleimide (Vulnoc PM, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.)
[0093] Co-crosslinking agent 3: Zinc methacrylate (Actor ZMA, manufactured by Kawaguchi Chemical Industries, Ltd.)
[0094] Cross-linking agent 1: (organic peroxide, Perhexa 25B-40, manufactured by NOF Corporation, purity 40% by mass)
[0095] Cross-linking agent 2: (organic peroxide, Peroxymon F-40, manufactured by NOF Corporation, purity 40% by mass)
[0096] Polyaramid staple fiber A: (RFL treatment, para-type, CFH3050 manufactured by Teijin, fiber diameter 12.3 μm, fiber length 3.0 mm)
[0097] Polyaramid staple fiber B: (RFL treatment, para-type, BKD7041E manufactured by Toray DuPont, fiber diameter 17 μm, fiber length 3.0 mm)
[0098] Nylon staple fiber: (RFL treatment, 6,6-nylon, CFN3000 manufactured by Asahi Kasei Corporation, fiber diameter 27.3 μm, fiber length 3.0 mm)
[0099] Polyaramid staple fiber A': (RFL of polyaramid staple fiber A is not treated)
[0100] (Evaluation method)
[0101] The double-toothed V-belts obtained in the examples and comparative examples were evaluated as follows. The results are shown in Table 2. In addition, the relationship between the storage elastic modulus and the elongation is shown in Table 2. Figure 2 .
[0102] <Storage elastic modulus E'>
[0103] A test piece with a size of 30 mm in the belt width direction, 10 mm in the belt length direction, and a thickness of 1 mm was cut out from the compression rubber layer of the double-tooth V-belt, and the storage elastic modulus E' at 25°C was measured by a tensile method based on JIS K6394: 2007. The measurement conditions were as follows: the strain at a load 1.3 times the load at a load strain of 1% was set as the average strain, the strain amplitude was set to 0.1%, the frequency was set to 10 Hz, and the test temperature was set to 25°C.
[0104] <Elongation EB>
[0105] A test piece having a length of 50 mm, a width of 10 mm, and a thickness of 1 mm was cut out from the compression rubber layer of the double-toothed V-belt, and the elongation at break at 25° C. was measured in accordance with JIS K6251:2017.
[0106] <Belt running test>
[0107] The belt running test was conducted using a continuously variable belt running test machine. In addition, the driven pulley was configured to be able to bear a constant load DW (dead weight) so that a constant belt tension was generated in the double-toothed V-belt.
[0108] Low-speed layout
[0109] A double-toothed V-belt was suspended and installed so that the winding diameter of the driving pulley was 99 mm and the winding diameter of the driven pulley was 263 mm. A constant load DW of 1800 N was applied to the driven pulley to generate belt tension, thereby forming a low-speed layout.
[0110] Thereafter, the driving pulley was rotated at 7500 rpm at an ambient temperature of 30°C to start low-speed belt operation. The belt operation was then continued until the double-tooth V-belt was cut, and the time from the start of the belt operation to the cutting was taken as the low-speed belt life. The maximum belt operation time was set to 200 hours.
[0111] High-speed layout
[0112] A double-toothed V-belt was suspended and installed with a winding diameter of 210 mm on the driving pulley and 165 mm on the driven pulley, and a constant load DW of 2300 N was applied to the driven pulley to generate belt tension, thereby forming a high-speed layout.
[0113] Thereafter, the driving pulley was rotated at 9400 rpm at an ambient temperature of 100°C to start high-speed belt operation. The belt operation was then continued until the double-tooth V-belt was cut, and the time from the start of the belt operation to the cutting was taken as the high-speed belt life. The maximum belt operation time was set to 50 hours.
[0114] [Table 2]
[0115]
[0116] The double-toothed V-belts obtained in Comparative Examples 1 and 2 had a short belt life in a low-speed layout, and the double-toothed V-belts obtained in Comparative Examples 3 to 5 had a short belt life in a high-speed layout and were inferior in durability.
[0117] On the other hand, the double-toothed V-belts obtained in Examples 1 to 6 of the present invention have a long belt life and excellent durability regardless of the low-speed layout or the high-speed layout.
[0118] Description of Figure Numbers
[0119] 1 Double-tooth V-belt
[0120] 10 With main body
[0121] 11. Rubber layer
[0122] 111 core wire
[0123] 12 Compression rubber layer
[0124] 12a Lower teeth
[0125] 121 Bottom reinforcement cloth
[0126] 13 Elongation rubber layer
[0127] 13a Upper teeth
Claims
1. A V-belt, characterized in that: The rubber layer is followed by a core wire embedded in the rubber layer and extending in the length direction of the belt; and A compression rubber layer is laminated on the inner circumference of the belt of the adhesive rubber layer. Regarding the rubber composition forming the compression rubber layer, when the value of the storage elastic modulus (E') at a dynamic strain of 0.1% strain measured by a tensile method at a frequency of 10 Hz and a test temperature of 25°C based on Japanese Industrial Standard K6394 of a rubber composition test piece collected in the belt width direction is X (MPa), and the value of the elongation of the rubber composition test piece collected in the belt length direction is Y (%), the following (1) and (2) are simultaneously satisfied: (1)X>800、 (2) Y>-42.05·ln(X)+340.
2. The V-belt according to claim 1, characterized in that The rubber composition includes the subsequently treated polyaramid short fibers.
3. The V-belt according to claim 1 or 2, characterized in that: The rubber composition contains an ethylene-α-olefin elastomer as a rubber component.
4. The V-belt according to claim 1 or 2, characterized in that: The rubber composition includes an unsaturated carboxylic acid metal salt.
5. The V-belt according to claim 1 or 2, characterized in that: It is a toothed V-belt.
Citation Information
Patent Citations
Transmission belt
JP2002081506A
Micron-nano short-fiber rubber composite material for automobile driving belt and method for preparing same
CN101555335A
Friction transmission belt
CN102203455A
Foam and foaming composition
CN103038275A
V-belt and production method therefor
CN105579741A